Risk and protective factors to prevent relapses of psychoactive substances users - Meire Luci da Silva; Camila Ferreira Guimarães; Daiane Bernardoni Salles (Rev Rene)
The objective of this study was to identify, in the perceptions of psychoactive substances users, protective and risk factors for relapses. Fifty users in treatment participated in this study in a therapeutic community in São Paulo, Brazil, in 2013. This is a qualitative study with the application of a self-administered questionnaire with closed questions and analysis through descriptive statistics. One identified as risk factors: lack of family support, family conflicts, negative feelings, social context, withdrawal from support groups, dissatisfaction with the treatment and financial difficulties. One highlighted as protective factors: religiosity, support groups, being the professional support one of the last support networks. One verified ambiguity of family and friends as a risk and protective factor. It is expected that the risk and protective factors identified may contribute to the prevention of relapse policies, enabling the enhancement of treatments focused on the recognition of protective factors, development of skills and coping strategies.